2012
DOI: 10.1093/annonc/mdr052
|View full text |Cite
|
Sign up to set email alerts
|

2-18fluoro-deoxy-D-glucose positron emission tomography (FDG-PET) for postchemotherapy seminoma residual lesions: a retrospective validation of the SEMPET trial

Abstract: Our study confirms the high specificity, sensitivity, and NPV of FDG-PET for evaluating postchemotherapy seminoma residuals. When carried out at an adequate time point, FDG-PET remains a valuable tool for clinical decision-making in this clinical setting and spares patients unnecessary therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(76 citation statements)
references
References 58 publications
1
67
0
8
Order By: Relevance
“…As false-positive findings may lead to unnecessary interventions, it is essential to conduct the scan at least 6 weeks after CT [15]. If the findings are equivocal, a follow-up scan can be performed before any intervention.…”
Section: Treatment Modalities For Csii Seminomamentioning
confidence: 99%
“…As false-positive findings may lead to unnecessary interventions, it is essential to conduct the scan at least 6 weeks after CT [15]. If the findings are equivocal, a follow-up scan can be performed before any intervention.…”
Section: Treatment Modalities For Csii Seminomamentioning
confidence: 99%
“…Ultimately, 21 studies were excluded for undesirable article types (n=21), not written in English (n=6), and insufficient data (n=4), letter (n=2), case report (n=1), and review (n=8). Thus, 16 studies were included in our final dataset for the meta-analysis (Cremerius et al, 1998;Albers et al, 1999;Cremerius et al, 1999;Hain et al, 2000;Bokemeyer et al, 2002;Spermon et al, 2002;Tsatalpas et al, 2002;Lassen et al, 2003;De Santis et al, 2004;Becherer et al, 2005;de Wit et al, 2008;Hinz et al, 2008;Oechsle et al, 2008;Akbulut et al, 2011;Bachner et al, 2012;Siekiera et al, 2012). The flowchart of study selection was shown in Figure 1.…”
Section: Study Selection and Characteristics Of Studies In Our Analysismentioning
confidence: 99%
“…Der PPV der FDG-PET Untersuchung lag in den vorliegenden Daten hingegen mit knapp 70% jedoch auch noch signifikant über dem der rein residualtumorgrößeabhängigen Therapiewahl (28%). Trotz allem ist hier noch ein signifikanter Schwachpunkt der Untersuchungsmethode zu sehen [2].…”
Section: Fdg-pet · Seminoma · Testicular Cancer · Residual Disease · unclassified